The Prevention of Noise Induced Hearing Loss in Children - Harrison, Robert V. (Hindawi Publishing Corporation, 2012)
Increasingly, our acoustic environment is filled with amplified sound sources (e.g., MP3 players, video game stations, and sports/entertainment venues). There is serious concern and also some controversy about the risks of acoustic trauma in children. This overview provides some basic information on the physiological mechanisms that lead to noise induced hearing loss, a survey of various studies that, on balance, indicates that there is cause for concern, and finally a discussion on measures that can help to prevent noise induced hearing loss in children. This paper is designed for public health and other healthcare professions (ENT, audiologists, family doctors, and pediatricians) who should understand the risks of noise induced hearing loss and its prevention.